Chemovirotherapeutic Treatment Using Camptothecin Enhances Oncolytic Measles Virus-Mediated Killing of Breast Cancer Cells - Tai, Chen-Jei (Sci Rep, 2019)
Oncolytic virotherapy represents an emerging development in anticancer therapy. Although it has been tested against a variety of cancers, including breast cancer, the efficacy of oncolytic viral vectors delivered as a monotherapy is limited. Enhancing viral oncolytic therapies through combination treatment with anticancer agents is a feasible strategy. In this study, we considered a chemovirotherapeutic approach for treating breast adenocarcinoma using oncolytic measles virus (MV) and the chemotherapeutic agent camptothecin (CPT). Our results demonstrated that co-treatment of MV with CPT yielded enhanced cytotoxicity against breast cancer cells. Low dosage CPT combined with MV was also found to elicit the same therapeutic effect as high doses of CPT. At the lower dosage used, CPT did not inhibit the early stages of MV entry, nor reduce viral replication. Further studies revealed that co-treatment induced significantly enhanced apoptosis of the breast cancer cells compared to either MV or CPT alone. Overall, our findings demonstrate the potential value of MV plus CPT as a novel chemovirotherapeutic treatment against breast cancer and as a strategy to enhance MV oncolytic activity.